OBLIGASI DAN SUKUK DALAM PERSPEKTIF KEUANGAN ISLAM - Jalil, Abdul (Ekonomi Syariah STAI Sangatta Kutai Timur, 2019)
In Islam, investment is a muamalah activity that is highly recommended, because investing in possessed assets becomes productive and also brings benefits to others. Investment by definition is investing or placing assets, both in the form of assets and funds in something that is expected to provide income or will increase in value in the future. While financial investment according to sharia can be related to trading activities. This paper will examine the investment instruments for Islamic bonds (sukuk) by looking at the contracts used and then comparing them to conventional bonds. Sukuk are in principle similar to bonds, with principal differences including the use of the concept of rewards and profit sharing as a substitute for interest, the existence of a supporting transaction in the form of assets that are the basis of the issuance, and the existence of a contract or agreement between the parties compiled based on sharia principles.